A robust supply chain planning framework for revenue management in the semiconductor industry. Issue 6 (December 2016) - Seitz, Alexander; Ehm, Hans; Akkerman, Renzo; Osman, Sarah
Abstract High demand uncertainties, long production lead times, and short product life cycles cause high risks for supply chain planning in the semiconductor industry. These affect all industries producing goods containing semiconductors. We present a robust supply chain planning framework for revenue management that consists of stable and flexible solutions for demand steering and dynamic pricing, extending current industry practice in several aspects. We introduce the concept of availabilities and capabilities, as well as various planning processes and process enablers. Based on our framework, we also highlight directions for future research.